KONSEP NASIONALISME DALAM AJARAN PAGUYUBAN PENGHAYAT KAPRIBADEN DI TULUNGAGUNG - Ramlan, Roni (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2018)
The background of this research starts from the issue of politicization of nationalism which during this time, the people only a look at it from the one perspective of intellectual elite which majority all of them have a legitimate religion. The narrow perspective makes the monopoly of monetary and policy occurred. It can discriminate and make the subordination in the diversity of spiritual religion that exist in the Nusantara. This research is a qualitative research by the ethnographical approach. Sources are obtained by the deep interview, participation of observation, and understanding about literature and documentation. The result of this research shows that the concept of Kapribaden nationalism can be indicated by two dimensions: textual and contextual. Textual dimension is the soul of nationalism that has identified through guyub rukun-manunggal doctrine and became the standard in the real life. Moreover, it consists as national agenda and should be celebrate it. Contextual agenda determines from implementation in the guyub rukun-manunggal doctrine in the social life. The doctrine materializes as a Laku and the transformation becomes the philosophical life in every Putro Romo.Keywords: Nationalism, Belief, Kapribaden Doctrine, Social Implication